Involvement of integrins alpha v beta 3 and alpha v beta 5 in ocular neovascular diseases. - Friedlander, M (1996)
Angiogenesis underlies the majority of eye diseases that result in catastrophic loss of vision. Recent evidence has implicated the integrins alpha v beta 3 and alpha v beta 5 in the angiogenic process. We examined the expression of alpha v beta 3 and alpha v beta 5 in neovascular ocular tissue from patients with subretinal neovascularization from age-related macular degeneration or the presumed ocular histoplasmosis syndrome or retinal neovascularization from proliferative diabetic retinopathy (PDR). Only alpha v beta 3 was observed on blood vessels in ocular tissues with active neovascularization from patients with age-related macular degeneration or presumed ocular histoplasmosis, whereas both alpha v beta 3 and alpha v beta 5 were present on vascular cells in tissues from patients with PDR. Since we observed both integrins on vascular cells from tissues of patients with retinal neovascularization from PDR, we examined the effects of a systemically administered cyclic peptide antagonist of alpha v beta 3 and alpha v beta 5 on retinal angiogenesis in a murine model. This antagonist specifically blocked new blood vessel formation with no effect on established vessels. These results not only reinforce the concept that retinal and subretinal neovascular diseases are distinct pathological processes, but that antagonists of alpha v beta 3 and/or alpha v beta 5 may be effective in treating individuals with blinding eye disease associated with angiogenesis.